On the human ethology of food sharing - Schiefenhövel, Wulf (Anthropological Review, 2014)
This paper compares various explanatory concepts of food sharing in humans. In many animal species, parents share food with their offspring, thus investing into the 50% of their own genes present in each child. Even in modern families of industrialised societies, there is a very significant flow of material goods from the parent to the offspring generation. Sharing food between reproductive partners is also easily explainable in evolutionary terms: „food for sex“ as male strategy is observed in some primate species. Sharing within one’s group in small-scale societies can be explained also as consequence of its members being actually rather closely related to each other; this, among others, gives credit to the concept of group selection which gains attention again after having been discarded by classic sociobiology. The ethos of individual and group sharing can quite readily be transferred to larger groups, i.e. a whole nation or, especially in the case of unusually devastating natural disasters, to members of other societies. Food sharing beyond genetic relationship or reproductive interest has been explained as „tit for tat“ and „reciprocal altruism“. Events of give and take, however, are, how the last example demonstrates, quite often non-symmetrical, i.e. one partner shares much more than the other. „Tolerated theft“, a behavioural trait in non-human primate species thought to be a stepping stone for the typical preparedness of humans to share, does not play a big role in traditional societies, which provide an important base to discuss the topic. The Trobriand Islanders, e.g., have a very complex system of sharing. In the years of competitive harvest, their yield of yam is distributed to close relatives, especially to fathers and elder brothers. The donors keep almost nothing for themselves, are however given as well, so that everybody has enough to live. High rank men receive a partly enormous surplus, by which their status is increased. Western farmers would find this generosity quite strange. It is one outcome of the human tendency to create bonds through food gifts. It is interesting, that Marcel Mauss has well described the power of the gift which generates a counter gift, but did not inquire evolutionary nor ontogenetic building blocks of the often very complex acts and rituals of giving and receiving one finds in all cultures. It seems reasonable to take an evolutionary position and argue that those of our ancestors who were generous and socially competent with a well-developed emphronesis (Theory of Mind) were preferred interaction and marriage partners and that this sexual selection was the ultimate mechanism spreading the motivations and behaviours involved in sharing. To counteract cheaters humans have a rather sharp perception to detect those who don’t play by the rules and a very strong motivation to punish them, even accepting, in doing so, high costs for themselves. This strongly disproves the idea that humans mainly act on rationale choice. Rather, we are endowed, one must conclude, with a very powerful, archaic sense of balanced social interaction, of fairness and justice. This raises the interesting question whether the laws governing social conduct, made by all cultures of the world, are contra or secundum naturam. For quite some time, in the wave of sociobiological thinking, the common stand was that humans are dangerously egoistic beings and that their antisocial instincts must be kept in check by powerful laws. As Irenäus Eibl-Eibesfeldt, the founder of human ethology as a discipline, has stated and as recent primatological and anthropological research has corroborated, humans are much more social than postulated by some authors. The Ten Commandments are built on not against basic human tendencies. Konrad Lorenz spoke of animals having “morally analogous” behaviours and was criticised for this. Modern research is rehabilitating him. The joy of sharing, a proximate behavioural set of motivation, is typical for our species. Notwithstanding expectations of economic and status gain this biopsychologically rooted tendency most likely is the engine driving the systems of do ut des, so marvellously developed in our species.